Medallion "Librarians in Time and Space". Krylov, librarian (1812 - 1841) (Confluenţe Bibliologice, 2025)
The article describes the significant influence that Ivan Krylov, a famous Russian fabulist, had on librarianship in Russia through his active promotion of reading and education.
Keywords: Krylov Ivan (1812 - 1841)